Planning of Heterogeneous Multi-Agent Systems Under Signal Temporal Logic Specifications With Integral Predicates - Buyukkocak, Ali Tevfik; Aksaray, Derya; Yazcoglu, Yasin (IEEE robotics and automation letters, 2021)
We address the problem of coordinating the trajectories of heterogeneous multi-agent systems under spatio-temporal specifications. In particular, we consider global Signal Temporal Logic (STL) constraints to express the number and type of agents that should be present at specific locations within the desired time windows. We also introduce an integral predicate to specify cumulative progress that can be achieved asynchronously by multiple agents. In order to generate optimal trajectories, we formulate a mixed-integer linear program whose objective is minimizing the agent movement subject to the heterogeneous abstracted dynamics of the agents and a global STL specification including the novel integral predicate. We demonstrate the performance of the proposed method via simulations and experiments with drones.